Perceived Organizational Support: A Meta-Analytic Evaluation of Organizational Support Theory - Kurtessis, James N.; Eisenberger, Robert; Ford, Michael T.; Buffardi, Louis C.; Stewart, Kathleen A.; Adis, Cory S. (Journal of Management, 2017)
Organizational support theory (OST) proposes that employees form a generalized perception concerning the extent to which the organization values their contributions and cares about their well-being (perceived organizational support, or POS). Based on hypotheses involving social exchange, attribution, and self-enhancement, we carried out a meta-analytic assessment of OST using results from 558 studies. OST was generally successful in its predictions concerning both the antecedents of POS (leadership, employee–organization context, human resource practices, and working conditions) and its consequences (employee’s orientation toward the organization and work, employee performance, and well-being). Notably, OST successfully predicted the relative magnitudes of different relationships, influences of process variables, and mediational effects. General implications of the findings for OST and research on POS are discussed.